Differential diagnosis for a mandibular mass – a rare case of an odontoameloblastoma in a red deer (Cervus elaphus elaphus) - Svenja Hartung; Kernt Köhler; Christiane Herden; Manfred Henrich (BMC Veterinary Research, 2021)
Abstract Background Mandibular masses caused by inflammatory processes due to bacterial infections, most common with Actinomyces bovis, are well known in herbivors. This case represents a rare differential diagnosis to common inflammatory processes which cannot be distinguished from neoplasia without detailed histopathological examination. Case presentation A large unilateral mandibular mass of a free-ranging female adult red deer (Cervus elaphus elaphus) was submitted for pathological examination. The animal had been shot due to its poor body condition. Grossly, the mandibular mass showed gingival ulceration and necrosis. Histologically, irregular strands and islands of odontogenic epithelial cells and a matrix of dentin and osteoid-like material were found, leading to the diagnosis of an odontogenic tumor. Considering the animal’s age the tumor was classified as odontoameloblastoma with secondary chronic purulent osteomyelitis. Conclusions Odontogenic tumors are rare in domestic and wildlife species and so far have not been reported in red deer. In addition to the more common inflammatory processes of the mandibula and other neoplastic diseases of the oral cavity, odontogenic tumors represent a rare differential diagnosis that must be kept in mind especially when masked by inflammatory lesions.